Relationship Between Tree Diversity and Carbon Stock in Muhammad Sabki Urban Forest, Jambi City, as Baseline Information for Regional Carbon Economic Value Development - Endri Kusno; Fazriyas Fazriyas; Mohd Zuhdi (Rifa'Institute, 2026)
Introduction: Urban forests play a critical role in biodiversity conservation, carbon storage, and climate change mitigation. Baseline data on vegetation diversity and carbon stock are essential for sustainable urban forest management and Carbon Economic Value (CEV) development Objective: This study aimed to analyze the relationship between tree vegetation diversity and carbon stock in Muhammad Sabki Urban Forest, Jambi City. Method: A quantitative descriptive-analytic approach was applied through a census of all trees with DBH ≥ 10 cm. Biomass, carbon stock, and CO₂-eq were estimated using allometric equations and standard conversion factors. The relationship between vegetation diversity and carbon stock was analyzed using Pearson correlation and simple linear regression. Results and Discussion: A total of 1,130 trees representing 29 species were recorded. Total aboveground biomass reached 269.531 tons, with carbon stock of 126.679 tons C equivalent to 464.913 tons CO₂-eq. Zone 2 had the highest carbon stock while Zone 3 showed the greatest species diversity. All vegetation diversity indices were positively correlated with carbon stock, with the Shannon-Wiener index showing the strongest relationship (r=0.592), followed by the Margalef index (r=0.441) and Pielou index (r=0.201). Conclusion: Tree vegetation diversity was positively associated with carbon stock in Muhammad Sabki Urban Forest. Carbon storage was influenced by both vegetation diversity and stand structure. The results provide baseline information for carbon inventory and regional Carbon Economic Value development